Impregnation of cellulose acetate films with carvacrol using supercritical carbon ioxide - Adamović Tijana N. (Tehnika, 2018)
Cellulose acetate films were impregnated with carvacrol using supercritical carbon dioxide. The supercritical impregnation process, conducted in a static regime at pressure of 21 MPa and temperature of 50°C, was optimized by variation in the processing time (30 and 120 min) and decompression rate (from 0.3 MPa/min to 36 MPa/min). Characterization of the obtained cellulose acetate films was performed by Atomic Force Microscopy and Differential Scanning Calorimetry. Effects of glycerol and carvacrol on the properties of the films were discussed. Release kinetics from the cellulose acetate film with 31.4% of carvacrol was investigated in a physiological saline solution. In addition, the Higuchi and Korsmeyer-Peppas release models fitted the carvacrol release curve well. Obtained cellulose acetate films impregnated with carvacrol can be of interest for the application in medicine as wound dressings considering their biocompatibility and biodegradability as well as their potential antimicrobial activity or in the food industry as an active food packaging.